The Management of Process of the Budget Area - Mora, Mayra Leonor Chancay; Triana, MarÃƒÂa Sonia Fleitas (International Research Journal of Management, IT & Social Sciences, 2018)
The budget area, of the Technical University of ManabÃ, has an organizational structure that is not coupled with the planning, because it has an organizational complexity according to its technical-administrative dimension, although it complies with all the organizational processes that involve the execution of the institutional budget taking into account the importance of human, material and technological resources, there are links in the budget execution program that are still weak. The research deals with the need to manage the budgetary processes, according to the activities that are planned within the Budget Area, with the objective of fulfilling the institutions priorities and strategies through the amounts assigned to its income and expenses, knowing that the budget planning and execution process is a fundamental tool to fulfill the mission and vision of Higher Education Institutions. The objective of the research is to look for alternatives that allow to solve the insufficiencies that exist in the management of the budgetary processes that affect the development of the activity, difficulties that appear both in income and in expenses; having as a result of these problems: rejections in the budgetary modifications, delays in the execution of the payment processes, actions that are fundamental for the execution of the institutional budget, which may affect the vision of the university.